France and Germany exceed Italy, South Korea and Japan in temperature-adjusted Corona proliferation: A quick and dirty Sunday morning analysis - Patrick A. Puhani (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2020)
Measures to contain the Corona virus (COVID-19) may pay off in terms of slowing down proliferation. The proliferation trend in France and Germany now exceeds the one in Italy, South Korea and Japan. At the same time, the containment measures seem more intense in Italy, South Korea and Japan than in France and Germany. Nevertheless, decision makers in France and Germany as in other countries need to compare the costs of containment (such as various forms of shut downs, cancellations of events, school closures, isolation, quarantine) with the costs of a faster proliferation of the virus. This is a 'quick and dirty Sunday morning' analysis of confirmed Corona cases as published in CSSEGISandData by the Johns Hopkins Whiting School of Engineering.
Keywords: I10; I18; 330; COVID-19; Corona outbreak; pandemic; epidemic; policy; quarantine; isolation